#### (i) (x + 3) (x + 5)

#### (ii) (x + 3) (x – 5)

#### (iii) (x – 7) (x + 9)

#### (iv) (x – 2y) (x – 3y)

**Answer :**

**(i) (x + 3) (x + 5)**

By further calculation

= x^{2} + (3 + 5) x + 3 × 5

So we get

= x^{2} + 8x + 15

**(ii) (x + 3) (x – 5)**

By further calculation

= x^{2} + (3 – 5)x – 3 × 5

So we get

= x^{2} – 2x – 15

**(iii) (x – 7) (x + 9)**

By further calculation

= x^{2} – (7 – 9)x – 7 × 9

So we get

= x^{2} + 2x – 63

**(iv) (x – 2y) (x – 3y)**

By further calculation

= x^{2} – (2y + 3y)x + 2y × 3y

So we get

= x^{2} – 5xy + 6y^{2}

**More Solutions:**

- Simplify the following (a + b)2 + (a – b)2
- Simplify the following (a + 1/a)2 + (a – 1/a)2
- Simplify the following (3x – 1)2 – (3x – 2) (3x + 1)
- Simplify the following (7p + 9q) (7p – 9q)
- Simplify the following (2x – y + 3) (2x – y – 3)
- Simplify the following (x + 2/x – 3) (x – 2/x – 3)
- Simplify the following (x + 2y + 3) (x + 2y + 7)
- Simplify the following (2p + 3q) (4p2 – 6pq + 9q2)
- Simplify the following (3p – 4q) (9p2 + 12pq + 16q2)
- Simplify the following (2x + 3y + 4z)